“Observation of 8 Graphoplastics techniques for teaching English to students from three to four years of age in initial level of “German Abdo Touma” primary school in the city of Riobamba, Chimborazo province in the academic year 2015-2016” - Arellano Sanaguano, Jessika Elizabeth (2016)
Why is it important used the techniques graph-plastics about the teaching a new language? Within the learning process of a new language, graph-plastics techniques help or support learning in children at the age of three to four. They also help when students apply different activities for learning the vocabulary, even though they have not developed their speaking skill totally. At this age kids have developed only the main abilities as; gross motors (body movements) and fine motors (muscle control - hands and shoulders). On the other hand, many authors consider that is important and necessary that children know English at early age, because at this stage assimilate new knowledge while listen, draw, speak, play, and imitate, these skills could help and involve them perform easily English language. it is not the same with the people at adult stage, because they tend to have difficulty and get confused in some features and structures of a new language. It is better that children can get all information which need to be clear and concise. The main objective of this project is to observe how the teacher uses graph plastics techniques in English class and provide some information in order to examine the importance using grapho plastics techniques in learning English language. This research lasted six months; through this time, a lot of information was gathered through an observation checklist containing important aspects to collect data regarding the teacher’s knowledge of some specific techniques that help in English language teaching; in addition, the checklist gathered information regarding students, and as to the class. Taking into account the main problem of this research which was of lack the knowledge about specific techniques for teaching English language; all this information help and gave support to develop this project: “Observation of 8 Grapho-plastics Techniques for Teaching English to students from three to four Years of age in initial level of “German Abdo Touma” Primary School in the city of Riobamba, Chimborazo province.